O mestu in vlogi slovenske književnosti v nemško govorečem prostoru / About the place and role of Slovenian literature in the German-speaking area - Borovnik, Silvija (Przekłady Literatur Słowiańskich, 2019)
Slovenian literature in Austria represents a case of multiculturality, but most of the time, biculturality and interculturality. The researchers claim that this type of literature belongs to Slovenian as well as to contemporary Austria nor German literature. It discusses and linguistically reflects on both cultural-historical environments. The literary translations show that the Slovenian literature in Austria has a double, Slovenian-German identity.